Validity and reliability of elastic resistance bands for measuring shoulder muscle strength. (17th May 2016) - Andersen, L. L.; Vinstrup, J.; Jakobsen, M. D.; Sundstrup, E.
Abstract : Valid and reliable measurements of muscle strength are important in sport medicine. This study assesses concurrent validity and intrarater reliability (test–retest reliability) of elastic resistance bands for measuring shoulder muscle strength. Altogether, 50 healthy adults [mean age 36.0 (SD: 11.6), 29 women and 21 men] participated in testing and retesting 1–2 weeks later. The maximal elastic resistance (TheraBand) that each participant could hold for 3 s during standing bilateral shoulder abduction to 90° was converted into torque and validated against gold standard maximal voluntary isometric contraction (MVC) (Vishay force transducer) performed unilaterally while lying supine. The intrarater reliability of both tests were high; for the MVC and elastic band test, respectively, ICC(3, 1) was 0.98 (95% CI: 0.97–0.99) and 0.99 (95% CI: 0.98–1.00), and measurement error was 4.8% (95% CI: 3.7–5.9) and 4.7% (95% CI: 3.1–6.2). For concurrent validity, ICC(3, 1) was 0.96 (95% CI: 0.95–0.98) and measurement error was 8.1% (95% CI: 6.6–9.6), and the elastic band test explained 93% of the variance in the MVC test. However, the elastic band test produced systematically lower torque values than the MVC [56.5 (SD: 26.8) vs 66.5 (SD: 25.5) Nm, P < 0.01]. In conclusion, the test for shoulder muscle strength using elastic resistance bands has excellent validity and reliability, but produces systematically lower torque values than MVC. The reason for the lower torque values may be that the elastic band test has an initial concentric phase and is performed bilaterally and standing upright.